Putting Data Privacy Regulation into Action: The Differential Capabilities of Service Frontline Interfaces - Steinhoff, Lena; Martin, Kelly D. (Journal of service research : JSR, 2023)
Service frontline encounters between customers and service providers have been subject to fundamental changes in recent years. As two major change agents, technology infusion and data privacy regulations are inextricably linked and constitute a critical ethical and societal issue. Specifically, service frontlines—as represented by human or technological agents, or some hybrid form—rely on customer data for service provision, which subjects them to privacy regulations governing the collection, submission, access, and use of any customer data thus captured. However, scant research outlines the significant implications of evolving data privacy regulations for service frontline encounters. To advance knowledge in this domain, this research distills six key dimensions of global data privacy regulations (fairness, data limits, transparency, control, consent, and recourse). Employing an intelligences theoretical lens, the authors theorize how these dimensions might become differentially manifest across three service frontline interface types (human-based, technology-based, and hybrid). Carefully intersecting the need for varying intelligences across data privacy regulatory dimensions with the abilities of service frontline interfaces to harness each intelligence type, this study offers a novel conceptual framework that advances research and practice. Theoretical, managerial, and policy implications unfold from the proposed framework, which also can inform a future research agenda.